Five-level three phase cascaded H-bridge inverter using digital signal processor control for renewable energy applications - Hiransing, Bancha; Wasuri, Boonthong; Kuankid, Sanya; Muangpool, Thanin (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This article presents a five-level three-phase cascaded H-bridge inverter for renewable energy applications, aimed at reducing total harmonic distortion (THD) and enhancing efficiency. The inverter uses a digital signal processing board, TMS320F28335, to generate pulse-width modulation signals through MATLAB/Simulink, ensuring precise control. The experimental setup includes an 84 VDC input voltage and a 300-watt load. Simulation and experimental results closely align, validating the accuracy of the simulation model. The output voltage shows a stepped pattern characteristic of multilevel inverters, significantly reducing harmonic distortion. THD analysis reveals a substantial reduction at higher modulation indices, with particularly low THD at a modulation index of 0.95. Consistent THD levels across modulation indices of 0.5, 0.8, and 0.95 demonstrate robust performance under varying conditions. Comparative analysis indicates that the proposed inverter achieves lower THD levels than traditional inverters, enhancing power quality and system efficiency. The five-level three-phase cascaded H-bridge inverter offers a promising solution for renewable energy applications by significantly reducing THD and improving power quality. Its robust performance and scalability potential contribute valuable advancements to renewable energy systems.